UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETIL ASETAT BIJI KESUMBA, FRAKSI ETIL ASETAT KUNYIT, DAN KOMBINASINYA - Asniati, Asniati; Rahmalia, Winda; Sayekti, Endah (Universitas Islam Indonesia, 2024)
Background: Antioxidants are compounds that can neutralize free radicals, so they can prevent degenerative diseases such as cardiovascular disease, carcinogenesis, and other diseases. Natural ingredients such as kesumba (Bixa orellana L.) seeds and turmeric (Curcuma longa L.) contain natural pigments that have antioxidant activity. Kesumba seeds contain bixin, and turmeric contains curcumin, each of which is an antioxidant compound that can protect cells in the body and prevent oxidative stress due to free radicals.Objective: To determine the effect of the combination ratio of the ethyl acetate fraction of kesumba seeds and the ethyl acetate fraction of turmeric on antioxidant activity.Method: Extraction was carried out by the maceration method, followed by fractionation. A qualitative test of the content of compounds in each extract and fraction of kesumba seeds and turmeric was carried out using the TLC method. The antioxidant activity test of each ethyl acetate fraction of kesumba seeds (FB) and ethyl acetate fraction of turmeric (FK) and their combination was carried out using the DPPH method.Result: The research showed that the antioxidant activity of the ethyl acetate fraction of kesumba seeds (FB) to the ethyl acetate fraction of turmeric (FK) was 242.95, 65.78, 42.48, 108.81, and 51.46 mg/L for each of the mass ratios (1:0), (3:7), (1:1), (7:3), and (0:1). The combination ratio of FB:FK, which is 1:1, has an effect on increasing antioxidant activity. This combination provides a synergistic effect that can increase antioxidant activity, with an IC50 value of 42.48 mg/L.Conclusion: Based on the results of the study, it can be concluded that the combination of the ethyl acetate fraction of kesumba seeds (FB) and the ethyl acetate fraction of turmeric (FK) has an effect on increasing antioxidant activity in the ratio of FB:FK (1:1) with an IC50 value of 42.48 mg/L, which is included in the very strong antioxidant category.Keywords: Kesumba seeds, turmeric, bixin, curcumin, antioxidant Intisari Latar belakang: Antioksidan adalah senyawa yang dapat menetralisir radikal bebas sehingga mampu mencegah penyakit-penyakit degeneratif seperti kardiovaskuler, karsinogenesis dan penyakit lainnya. Bahan alam seperti biji kesumba (Bixa orellana L.) dan kunyit (Curcuma longa L.) mengandung pigmen alami yang memiliki aktivitas antioksidan. Biji kesumba mengandung bixin dan kunyit mengandung kurkumin yang masing-masing merupakan senyawa antioksidan sehingga mampu melindungi sel-sel dalam tubuh dan mencegah stress oksidatif yang diakibatkan oleh radikal bebas. Tujuan: Untuk mengetahui pengaruh rasio kombinasi fraksi etil asetat biji kesumba dan fraksi etil asetat kunyit terhadap aktivitas antioksidan.Metode: Ekstraksi menggunakan metode maserasi dan dilanjutkan dengan fraksinasi. Uji kualitatif kandungan senyawa dalam masing-masing ekstrak dan fraksi bixin dan kurkumin dilakukan menggunakan metode kromatografi lapis tipis (KLT). Uji aktivitas antioksidan masing-masing fraksi etil asetat biji kesumba dan fraksi etil asetat kunyit serta kombinasinya dilakukan menggunakan metode DPPH.Hasil: Hasil penelitian menunjukkan bahwa tiap kombinasi rasio massa fraksi etil asetat biji kesumba (FB); fraksi etil asetat kunyit (1:0), (3:7), (1:1), (7:3) dan (0:1) memiliki aktivitas antioksidan berturut-turut sebesar 242,95; 65,78; 42,48; 108,81; dan 51,46 mg/L. Kombinasi tersebut memberikan efek sinergis yang dapat meningkatkan aktivitas antioksidan dengan nilai IC50 sebesar 42,48 mg/L. Kesimpulan: Berdasarkan hasil penelitian dapat disimpulkan bahwa pada kombinasi fraksi etil asetat biji kesumba (FB) dan fraksi etil asetat kunyit (FK) dengan rasio FB:FK (1:1) memberikan pengaruh pada peningkatan aktivitas antioksidan dengan nilai IC50 sebesar 42,48 mg/L yang termasuk dalam kategori antioksidan sangat kuat.Kata kunci: Biji kesumba, kunyit, bixin, kurkumin, antioksidan